2016
DOI: 10.1158/0008-5472.can-15-0701-t
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent MLK4 Loss-of-Function Mutations Suppress JNK Signaling to Promote Colon Tumorigenesis

Abstract: MLK4 is a member of the mixed-lineage family of kinases that regulate the JNK, p38, and ERK kinase signaling pathways. MLK4 mutations have been identified in various human cancers including frequently in colorectal cancer, where their function and pathobiological importance has been uncertain. In this study, we assessed the functional consequences of MLK4 mutations in colon tumorigenesis. Biochemical data indicated that a majority of MLK4 mutations are loss-of-function (LOF) mutations that can exert dominant n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
(34 reference statements)
2
32
0
Order By: Relevance
“…These results are consistent with previous reports that MLK4 functions as a negative regulator of p38 and JNK signalling in HCT116 colon cancer cells, and negatively regulates Toll receptor signalling and LPS-induced ERK and JNK activation in murine macrophages [3, 4]. However, the results are contrary to findings that MLK4 is an activator of JNK in HCT15 colon cancer cells [14]. These studies employed different cell types that were cultured under different adherence conditions, and possibly the variation in these critical parameters influenced the effect of MLK4β expression on MAPK activation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with previous reports that MLK4 functions as a negative regulator of p38 and JNK signalling in HCT116 colon cancer cells, and negatively regulates Toll receptor signalling and LPS-induced ERK and JNK activation in murine macrophages [3, 4]. However, the results are contrary to findings that MLK4 is an activator of JNK in HCT15 colon cancer cells [14]. These studies employed different cell types that were cultured under different adherence conditions, and possibly the variation in these critical parameters influenced the effect of MLK4β expression on MAPK activation.…”
Section: Discussionsupporting
confidence: 91%
“…MLK3, the most extensively studied member of the MLK subfamily, has critical functions in migration and invasion in breast, gastric, and ovarian cancer cells; and MLK3 regulates neuronal cell apoptosis [912]. MLK3 has more than 70% sequence identity to the MLK4 catalytic domain; however, recent studies indicate non-redundant functions of these enzymes in normal and neoplastic cells [3, 4, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant expression and activation of JNK are often observed in many cancer cell lines and in patient tissues [27]. The role of JNK is controversial, as it has been shown to be a positive regulator of CRC metastasis as shown in this study and other reports [14, 42], whereas other studies demonstrated a role of JNK as a tumor suppressor in CRC [43]. Studies in mice have demonstrated that the contribution of JNK is cell type and isoform specific, which may explain the seemingly opposite role of JNK in promoting cell survival and proliferation on one hand and cell death on the other [25].…”
Section: Discussionmentioning
confidence: 58%
“…In the pan-cancer analyses we found only a single novel SMG, which was not either present in the curated COSMIC Cancer Gene Census or found by Martincorena et al 26 . This gene, MLK4 (q=2e -4 ), is a mixed lineage kinase that regulates the JNK,P38 and ERK signaling pathways and has been reported to inhibit tumorigenesis in colorectal cancer 27 . In addition, in our tumor type-specific analyses, which for several tumor types is limited by the number of samples, we identified a novel metastatic breast cancer-specific SMG -ZFPM1 (also known as Friend of GATA1 (FOG1), q=8e -5 ), a zinc-finger transcription factor protein without clear links with cancer.…”
Section: Significantly Mutated Genesmentioning
confidence: 99%